Analysis of the Importance of Microbiota in the Human Body in the Formation of Immunity or Immune Reactions - Abdullaevna, Kadirova Kuralay; qizi, Norkulova Mubinabonu Turgun; Farkhodovich, Abdurazakov Dzhurabek; Furkatovich, Raufov Saidamir; ugli, Buronboev Khafizullo Sardor (American Journal of Bioscience and Clinical Integrity, 2024)
Microbiota are important for the formation, training and functioning of the host's immune system, including the human body. In turn, the immune system has largely evolved to support the symbiotic interaction of the host with these extremely diverse and evolving microbes. When the immune system and microbiota work together perfectly, they can trigger protective responses to pathogens and support regulatory mechanisms that help maintain tolerance to harmful antigens. But in high-income countries, the microbiota has become less diverse and resilient due to the overuse of antibiotics, dietary changes and the disappearance of such permanent partners as nematodes. All this is necessary for the formation of balanced immune responses. It is assumed that this phenomenon is partly due to the sharp increase in the number of autoimmune and inflammatory diseases in those areas of the world where our symbiotic relationship with the microbiota has been most affected. We will talk about what we know today about the causal interactions of the host immune system and the microbiome, the problems and limitations we face, and how they affect immune-mediated diseases. We also discuss how this data can be used to develop future therapeutic interventions targeting the microbiome.